1981
DOI: 10.1161/01.res.49.6.1319
|View full text |Cite
|
Sign up to set email alerts
|

The effects on atrial electrophysiology and structure of surgically induced right atrial enlargement in dogs.

Abstract: We evaluated the relationship between susceptibility to arrhythmias caused by right atrial (RA) enlargement and alterations in transmembrane potentials and ultrastructure. RA enlargement was produced in eight dogs (TI) by excising the septal cusp of the tricuspid valve through a right atriotomy and constricting the pulmonary artery. This procedure resulted in RA dilation and hypertrophy. Four sham-operated dogs (S) also were studied. Neither TI nor S dogs developed spontaneous atrial arrhythmias. Atrial overdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
6

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(49 citation statements)
references
References 32 publications
0
43
0
6
Order By: Relevance
“…Experimental data suggest that atrial enlargement and hypertrophy create the requisite milieu for AF. 16 The use of P-wave SAECG in this population will need to be confirmed in other populations before these results can be extrapolated. Other high-risk populations, such as patients with valvular heart disease, hypertension, or coronary heart disease, may be suitable candidates.…”
Section: P-wave Saecg Resultsmentioning
confidence: 92%
“…Experimental data suggest that atrial enlargement and hypertrophy create the requisite milieu for AF. 16 The use of P-wave SAECG in this population will need to be confirmed in other populations before these results can be extrapolated. Other high-risk populations, such as patients with valvular heart disease, hypertension, or coronary heart disease, may be suitable candidates.…”
Section: P-wave Saecg Resultsmentioning
confidence: 92%
“…The first animal studies were performed in the early 1980s by Boyden and Hoffman. 16 In 8 dogs with tricuspid regurgitation and stenosis of the pulmonary artery, RA volume increased by 40%. Spontaneous atrial arrhythmias did not occur, but the inducibility and duration of atrial tachyarrhythmias were higher.…”
Section: Discussionmentioning
confidence: 98%
“…Alterations in atrial cellular electrophysiology have been reported in patients [2][3][4][5][6] and experimental animals 7,[15][16][17] with atrial disease and/or dilation. Similar to our observations at slower rates, APD was not substantially altered in dogs with tricuspid insufficiency 15 and chronic mitral regurgitation. 16 Cats with endogenous cardiomyopathy had APDs that were either unchanged or (in more severe cases) increased in the left atrium.…”
Section: Comparison With Previous Studies Of Cellular Electrophysiolomentioning
confidence: 99%